A case of oligoarthritis juvenile idiopathic arthritis in a 3-year-old male child: challenges in early diagnosis and management - Heksa Trisnawati; Farhan Ardiyanta Setyagisna; Muhammad Reva Aditya; Wisnu Barlianto; Desy Wulandari (Pediatric Sciences Journal, 2025)
Introduction: Juvenile Idiopathic Arthritis (JIA) is the most common chronic rheumatic disease in children, characterized by persistent joint inflammation. However, early diagnosis is often challenging due to heterogeneous clinical manifestations. Among its subtypes, oligoarthritis is the most common, involving up to four joints within six months of symptom onset. This case is distinctive due to its very early onset at the age of 3 years, prolonged diagnostic delay despite multiple healthcare visits, and diagnostic challenges related to nonspecific initial symptoms. Delayed diagnosis can result in joint deformity, growth retardation, and long-term disability, highlighting the importance of early recognition and timely management. Case Presentation: A 3-year-old male child presented with progressive joint pain, morning stiffness, and recurrent joint swelling that was initially associated with a history of trauma. Symptoms had been present since the age of 1.5 years, leading to a significant delay in definitive diagnosis. Based on clinical evaluation, imaging findings, and laboratory investigations, a diagnosis of oligoarticular Juvenile Idiopathic Arthritis was established according to the International League of Associations for Rheumatology (ILAR) criteria. The diagnostic process was further complicated by trauma-associated symptom onset and involvement of the temporomandibular joint (TMJ), which underscores the need for heightened clinical suspicion. The patient received multidisciplinary management, including pharmacological therapy, physical rehabilitation, and nutritional support. Conclusion: This case illustrates the complexity of diagnosing and managing oligoarticular JIA in pediatric patients, particularly in cases with very early onset, delayed diagnosis, and TMJ involvement. A comprehensive multidisciplinary approach, along with increased clinical awareness and early diagnosis, is essential to control inflammation, preserve joint function, and prevent long-term complications in children with JIA.